EKUMENISME AKAR RUMPUT - Silvana Natalia Nainggolan; Martin Dendo Ngara (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2026)
The charismatic prayer movement has been an important part of the spiritual life of Christians in Indonesia since the late 20th century. This practice has sparked debate about its compatibility with Church denominational teachings and its impact on ecumenical efforts. This study aims to examine how the charismatic prayer movement influences interdenominational relations among Churches in Indonesia. This study uses descriptive qualitative research with the help of quantitative data analysis. Data was collected through a Google Form survey from all Church denominations in Indonesia. The survey results show that the majority of respondents accept the charismatic prayer movement and see it as a potential ecumenical bridge between church denominations. However, rejection and concerns also arise, particularly regarding theological confusion and liturgical incompatibilities within each church's tradition